The Impact of Democracy Education on the Success of Conflict Management in Kediri District - Susilo, Suko (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
The purpose of this study was to determine the impact of democracy Education on efforts to handle, prevent, and recover from post-economic, political, and social conflicts in East Java, precisely in Kediri Regency. The research method used is qualitative. The research technique used is joint research that is the normative-empirical study and social science to know how the implementation of the democracy education of the people of Kediri Regency. The findings revealed that the application of democratic education had an impact on the economic, political, and social conflict management of the people of Kediri Regency. Especially from the life of the town during the General Election period (PEMILU), Regional Head Election (PILKADA), and Village Head Election (PILKADES), which seemed more peaceful than in the Era of Political Dynasty. The economic and social life of the community is much better now, especially during the social distancing policy, the town can survive economically and get involved in handling Covid-19. Kediri regency shows that social tolerance is extreme. This research is to be able to contribute to the future of the legal and policy bodies of the local government of the Kediri regency in handling economic, political, and social conflicts that exist in the community. In the end, the law and the democratic system can minimize intolerance and lawless behavior that can hamper economic development.